Implementation of the Utilization of Social Media by Islamic Religious Extension Workers of KUA Rembang as a Means of Public Communication in the Perspective of the ITE Law - Achmad Shiva’ul Haq Asjach; Suparnyo Suparnyo (Jurnal Impresi Indonesia, 2026)
This research aims to analyze the implementation of social media utilization by Islamic religious counselors at the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Rembang District as a medium of public communication and to examine its conformity with the provisions of the Electronic Information and Transactions Law. This research employed an empirical juridical method with a qualitative approach. Primary data were obtained through interviews and observations of the social media activities conducted by Islamic religious counselors, while secondary data were collected through library research involving laws and regulations, books, scientific journals, and other supporting documents. The results indicate that social media platforms such as WhatsApp, Facebook, Instagram, and TikTok have been actively utilized as tools for disseminating religious information, Islamic legal education, KUA administrative services, and digital-based public communication. The use of social media has contributed to improving the effectiveness of public services by enabling information to be delivered more quickly, broadly, and interactively to the community. From a legal perspective, the implementation of digital public communication by Islamic religious counselors has generally been carried out in accordance with educational and public service functions; however, it still requires strengthening in aspects of digital literacy, information verification, communication ethics, and understanding of electronic law provisions as regulated under the Electronic Information and Transactions Law (UU ITE). Therefore, capacity building through digital literacy and cyber law training, along with the formulation of social media guidelines, is necessary to ensure professional, responsible, and legally compliant digital public communication.